Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3144/expresspolymlett.2015.51
|View full text |Cite
|
Sign up to set email alerts
|

Combined main-chain/side-chain ionic liquid crystalline polymer based on ‘jacketing’ effect: Design, synthesis, supra-molecular self-assembly and photophysical properties

Abstract: Ionic liquid crystalline polymers (ILCPs) are a class of macromolecular architectures with mesogenic groups and ionic species and they have attracted great interest in the fields of polymer chemistry and materials science lately [1][2][3]. The combination of electrostatic interaction with liquid crystalline (LC) ordering yields ILCPs with excellent mechanical properties, rheological processability, piezoelectric performance, and optical variable performance [1][2][3][4][5][6][7]. Generally, ionic interaction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Ionic polymers are generally synthesized either by solution polymerization of various ionic monomers or bulk polymerization in the case that ionic liquid monomers are applied . Ionic liquid monomers are ionic liquids that are substituted with a polymerizable functional group.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic polymers are generally synthesized either by solution polymerization of various ionic monomers or bulk polymerization in the case that ionic liquid monomers are applied . Ionic liquid monomers are ionic liquids that are substituted with a polymerizable functional group.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the liquid‐crystalline behavior of ILCs depends on the nature of the cations and anions that the ILCs have . Some typical cations ILCs with pyridinium, imidazolium, pyrrolidinium, quaternary ammonium, and quaternary phosphonium salts have been reported, as well as anions ILCs with BF 4 − , PF 6 − , CF 3 SO 3 − , and so on . These organic cations and organic/inorganic anions interact via electrostatic and other noncovalent interactions rather than covalently bound .…”
Section: Introductionmentioning
confidence: 99%